Evaluación potencial maderable y valoración económica del bosque de colinas bajas suavemente accidentada de la zona de Buen Jardín, distrito del Yavarí. Región Loreto 2019 - Vasquez Peña, Christina Katihusca (2020)
The study was carried out in the gently hilly low hills forest [BCbI] of the Buen Jardín Yavari District - Loreto Region. The objectives were to record the potential or floristic composition of commercial timber species with diameter ? 40 cm; determine the IVI; define the volume of standing commercial timber, the economic valuation and identify the current and potential use of the commercial species recorded per ha and total. The design for the forest inventory of PC 01 was that of Fajas, systematically distributed, using plots of 100 m wide by 1000 m long x 1.5 m. width of separation between strips (sampling unit), making a total of 25 sampling units, in the same way for PC 2, 11 commercial species were found, distributed in 7 botanical families. The largest number of species is in the botanical family Fabaceae (0.33%). The representative species, according to the IVI are, "cumala, aguanillo and screw" and the species with a lower IVI are, "mari mari and andiroba" The volume of commercial wood studied in PC 1 with 1 320.19 m3 in 250 hectares and in PC 2 also with 250 hectares and 1,429.36 m3, making a total of 2,749.82 m3 in the 500, resulting in 5.49 m3 / ha. The potential use of the identified species are: sawmill, rolling; buildings; parquet and tanner, being the screw species with the highest value S /. 64 128.04 of PC1 and PC2 with the same species with a value of S /. 76 243.07